Motivasi Orang Tua Menyekolahkan Anak di SMP IT Darul Muta'allimin Meulaboh - Dahri Dahri; H. M. Arif Idris (Tadabbur: Jurnal Peradaban Islam, 2022)
The study in this thesis research departs from efforts to see how the motivation and interest of parents of students in sending their children to SMP-IT Darul Muta'allimin, Meulaboh. Parents have a big role in determining the direction of their children's education, including in selecting schools for their children. This thesis is entitled Motivation of Parents to Send Their Children to SMP IT Darul Mutallimin, Meulaboh. (1) To find out why SMP IT Darul Muta'allimin is the choice of parents in sending their children to school (2) To find out what are the motivations of parents in sending their children to SMP IT Darul Muta'allimin. Data collection in this study was carried out using a qualitative method approach, in which researchers began to get involved from observing the motivation of parents to send their children to SMP IT Darul Mutallimin, conducting in-depth interviews with parents who had been selected as samples in this study, documenting several pictures. which are considered important as research data, to the data analysis process which is carried out by sorting and selecting data that is considered to have a relationship with the theme of this thesis. The results of the study show that among the motivations of parents of students to send their children to the Darul Mutallimin Islamic Boarding School, it is due to several factors, including because the trend of sending their children to Islamic boarding schools has become a trend and parents choose education that is combined with religious values ​​as a solution to social change. In addition, graduates of integrated Islamic boarding schools are considered to have additional skills, and are more independent for children to live their lives after they have completed their education there.